Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ma13235365
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of a Double-Layer Chitosan Coating on Cotton Fabric to Improve the Color Fastness of Sodium Copper Chlorophyllin

Abstract: Natural dye’s poor affinity for cotton and poor fastness properties still hinder its applications in the textile industry. In this study, a doubled-layered chitosan coating was cured on cotton fabric to serve as bio-mordant and form a protective layer on it. Under the optimal treatment conditions, the maximum qe (adsorption amount) of the natural dye sodium copper chlorophyllin (SCC) calculated from the Langmuir isothermal model was raised from 4.5 g/kg to 19.8 g/kg. The dye uptake of the treated fabric was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Similar findings had already been reported previously where the WI was decreased upon treating the non-woven cotton matrix with aloe vera oil microcapsules [ 23 ]. Slight changes in the WI may be attributed to the thermal curing of the chitosan layer on the treated fabric which could cause a yellowing effect [ 24 ]. The application of Artemisia Afraoil microcapsules could also reduce the WO of the treated fabric [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings had already been reported previously where the WI was decreased upon treating the non-woven cotton matrix with aloe vera oil microcapsules [ 23 ]. Slight changes in the WI may be attributed to the thermal curing of the chitosan layer on the treated fabric which could cause a yellowing effect [ 24 ]. The application of Artemisia Afraoil microcapsules could also reduce the WO of the treated fabric [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Later on, Zhao et al. 209 cured cotton fabric with a doubled-layered CS coating to serve as bio-mordant for the natural dye, sodium copper chlorophyllin (SCC). They found that the maximum q e (adsorption amount) of SCC calculated from the Langmuir isotherm model was increased from 4.5 to 19.8 g/kg.…”
Section: Chitosan As An Auxiliary Agent In Dyeing and Printing Processesmentioning
confidence: 99%
“…The cotton fabrics treated with chitosan not only provide better depth of shade but also give better wash and light fastness than those of the untreated fabrics dyed with Roselle. In order to dye cotton fabric with natural dye sodium copper chlorophyllin (SCC), Zhao et al [125] used ChSN as a double-layered fabric coating to serve as bio-mordant. They found that the maximum qe (adsorption amount) of SCC calculated from the Langmuir isothterm model was raised from 4.5 g/kg to 19.8 g/kg.…”
Section: Eco-friendly Dyeing With Chitosanmentioning
confidence: 99%